Biology of the black clam, Villorita cyprinoides (Gray) in the backwaters of Vembanad Lake - Laxmilatha, P; Velayudhan, T S (Indian Journal of Fisheries, 2011)
Biology of the black clam from two fishing sites of the Vembanad Lake wasstudied. The environmental conditions of the two sites were also monitored.The observed differences in the growth pattern and breeding biology of theblack clam from Nettoor and Muhamma are correlated to the hydrologicalparameters. These characteristics are discussed.